Cognitive performance in asymptomatic carriers of mutations R1031C and R141C in CADASIL (2018)
ABSTRACT: CADASIL is the most common hereditary cause of repeated ischemic strokes, and has also been identified as a model of pure vascular dementia. The objective of this study was to establish the cognitive performance of asymptomatic carriers with the mutations R1031C and R141C. This observational cross-sectional analytical study divided subjects into three groups: asymptomatic carriers of the R1031C mutation (=39), asymptomatic carries of the R141C mutation (=8) and non-carriers (=50). Statistically significant differences were found (<0.05) between the group of the R1031Cmutation and the non-carriers in constructional praxis, executive function and abstract reasoning. For the R141Cmutation, scores below expected values in executive function and mental calculation were observed. It is concluded that asymptomatic carriers of the two mutations showed low performance in working memory, mental abstraction and processing speed, which could be associated with preclinical cognitive biomarkers preceding the presentation of the first vascular event.